The relationship between Islamic religiosity, work engagement and job performance - Zahrah, Novia; Aziz, Azelin; Abdul Hamid, Siti Norasyikin (2017)
Numerous researches on the influence of work engagement on job performance have been conducted. Yet little research have considered the role of Islamic religiosity at the workplace in affecting job performance.Whereas, job performance and engagement of a Muslim should be examined based on Islamic perspective in order to sustain the productivity of a Muslim in dealing with hardships.For the reason that Islam obligates all Muslim to perform the trust (amanah) given and work as a form of worship.While in dealing with difficulties, a Muslim is obligated to be patient, self-control, tawakal (trust) to Allah’s will, and believe that there is great wisdom behind everything that Allah does.These obligations can be fulfilled through the Islamic religiosity.In fulfilling these obligations, the individual will put the best effort to engage and simultaneously perform as well as possible.Thus, in response to the impact of Islamic religiosity in enhancing work engagement and sustaining job performance, this study is conducted to fill the gap by investigating the mediating role of work engagement on the relationship between Islamic religiosity and job performance of Muslim employees.The proposition of this study demonstrates the significant role of mediation of work engagement on the relationship between Islamic religiosity and job performance were found to be significant.Implications of the study for management and suggestions for future research are presented.This study recommends management and human resource practitioners to be proactive and formulate preventive strategy against low productivity among Muslim employees by provides training, create an environment that supports wholeness, meaningful work, and feeling of inner satisfaction. However, there is need for empirical studies to test the proposed relationships.